Masculinização da população rural no Rio Grande do Sul análise a partir dos sistemas agrários - Rauber, Cassiane da Costa (2010)
This study aimed to examine the masculinity index of the rural population in the different agrarian systems of Rio Grande do Sul (Brazil) verifying possible features and different settings. Systematic and statistical analysis of data from the IBGE Population Count referring to the rural population in Rio Grande do Sul by district in 1950 and by municipalities in 2007 were performed. Masculinity indices of the total rural population and of four age groups were calculated (children, young people, adults and seniors). For the application of Kruskal-Wallis test the rates were grouped by land system (1 Campanha; 2 - Serra do Sudeste; 3 - Depressão Central; 4 Litoral Norte; 5 Litoral Sul; 6 Colonias Velhas; 7 Campos de Cima da Serra; 8 Colônias Novas and 9 - Planalto). Regarding data from 2007, the Test for Difference between Two Proportions was applied. Since 1950 the process of rural masculinization has been intensifying in Rio Grande do Sul, however, it is not a process that takes place homogenously throughout the state, that is, it presents different behaviors depending on the different farming systems. In 1950 and 2007 the agrarian systems 1 and 5 were considered the most masculine. In 2007, the processes 2 and 7 also intensified, and in the cited systems the extensive livestock farming was highly representative. There is a tendency of differentiation in the indices of masculinity of these agrarian systems in relation to the systems 6, 8, 3, and 9. The agrarian systems 9 and 3, where the mechanized production of soybean and rice is representative, underwent a transformation in the behavior in the period, assuming an intermediate position between the high levels of masculinity in the cattle-raising region and low levels in the Colônias, where the family agriculture is a relevant. No significant differences were observed among the agrarian systems in the strata of children and young people, whereas for the adult population there was a clear differentiation of behavior. This differentiation is accentuated among the elderly, where the agrarian systems present three different behaviors: 1) moderate female predominance of family farming in the regions, 2) moderate male predominance in the region of mechanized agriculture, 3) intense male predominance in cattle-raising regions. Thus, the socioeconomic importance of family farming in the agrarian system, the characteristics of the production process, the relations of production, land concentration, and intensity of the main systems of production seem to influence the behavior of rural masculinization especially among the elderly. From the results of the quantitative analysis, a new literature review was performed as a complementary study, checking alternatives to rural masculinization suggested by different authors and policymakers in Brazil. Based on the research data we discussed the relevance and adaptability of these alternatives to the agrarian systems of Rio Grande do Sul. This literature presents important discussions, however it is too generic. In this sense, some alternatives have been suggested highlighting the need for strengthening family agriculture through land reform, especially in some regions in the state.